Arthroscopic Hip Labral Reconstruction With Fresh Meniscal Allograft - Julia J. Beyer, M.D.; Jarod A. Richards, M.D.; David R. Woodard, M.D.; James L. Cook, D.V.M., Ph.D.; Brett D. Crist, M.D.; Steven F. DeFroda, M.D., M. Eng. (Arthroscopy Techniques)
The acetabular labrum functions to protect the overall health of the hip joint through maintenance of joint biomechanics and the fluid suction seal, which decreases stress and strain on the cartilage. Labral reconstruction has emerged as a promising treatment option for the management of irreparable labral pathology. Meniscal allograft has been considered an option for labral reconstruction due to its structural and functional similarities to the native labrum. We present an arthroscopic technique for labral reconstruction using fresh meniscal allograft. A nonviable residual labrum in the setting of pain is the primary indication for this treatment. The open application of this meniscal transplantation technique has resulted in a higher initial success rate, superior patient-reported outcomes, and subjectively better magnetic resonance imaging tissue incorporation than tibialis anterior transplantation controls. The native hip labrum is more similar to meniscal tissue than tendon tissue at biomechanical and cellular levels. Meniscal tissue is naturally load-sharing, which makes it a better tissue for hip labral reconstruction. Cellular, biomechanical, and outcome analyses are underway to further investigate this technique.